Analisis Sistem Informasi Manajemen Perkuliahan pada Fakultas Ilmu Komputer Universitas Sriwijaya - Mgs Afriyan Firdaus; Firdaus -; Ali Bardadi (Universitas Sriwijaya, 2010)
One of the main tasks of Computer Science Faculty of Sriwijaya University (Fasilkom Unsri) as one of the higher education institution is the academic management. Academic process in Fasilkom Unsri still emphasizes the use of word processing and spreadsheet applications that can result in delays and redundancy on the processing of data for syllabus, units lecture event, teachersâ€™ attendance, and class schedules reports. The absence of a specialized system that monitors the lecture materials directly can also result in decision making process by the top-level-management becomes less optimal to improve the quality of higher education in the academic field. Development of Course Management Information Systems is an effort to facilitate the top-level-management (Dean, Assistant Dean) in business management and evaluation of the overall college process that has occurred in order to improve the quality of higher education in the academic field using computer-based systems.This study emphasizes the process of developing course management information systems at Fasilkom Unsri, particularly in systems analysis phase. The methodology used is the Framework for the Application of Systems Thinking (FAST). In this methodology there are some systems analysis processes, namely the scope definition, problem analysis, requirements analysis, logical design and decision analysis.This study produced a proposed system and application architecture of management information systems courses in Fasilkom Unsri. Â Keywords: course management information system, user interface, Framework for the Application of Systems Thinking (FAST), system analysis